Assessment of foot alignment and function for ambulatory children with cerebral palsy: Results of a modified Delphi technique consensus study. (April 2022) - Davids, Jon R; Shilt, Jeff; Kay, Robert; Dreher, Thomas; Shore, Benjamin J; McCarthy, James; Shrader, Wade; Graham, Kerr; Veerkamp, Matthew; Narayanan, Unni; Chambers, Hank; Novacheck, Tom; et al.
Purpose: The purpose of this study was to establish consensus for the assessment of foot alignment and function in ambulatory children with cerebral palsy, using expert surgeon's opinion through a modified Delphi technique. Methods: The panel used a five-level Likert-type scale to record agreement or disagreement with 33 statements regarding the assessment of foot alignment and function. Consensus was defined as at least 80% of responses being in the highest or lowest of two of the five Likert-type ratings. General agreement was defined as 60%–79% falling into the highest or lowest two ratings. There was no agreement if neither threshold was reached. Results: Consensus was achieved for 25 (76%) statements, general agreement for 4 (12%) statements, and lack of consensus for 4 (12%) of the statements. There was consensus that the functional anatomy of the foot is best understood by dividing the foot into three segments and two columns. Consensus was achieved concerning descriptors of foot segmental alignment for both static and dynamic assessment. There was consensus that radiographs of the foot should be weight-bearing. There was general agreement that foot deformity in children with cerebral palsy can be classified into three levels based on soft tissue imbalance and skeletal malalignment. Conclusion: The practices identified in this study can be used to establish best care guidelines, and the format used will be a template for future Delphi technique studies on clinical decision-making for the management of specific foot segmental malalignment patterns commonly seen in children with cerebral palsy. Level of Evidence: V